1571. Cost-Effectiveness Analysis of Duration of Valganciclovir Prophylaxis Among CMV Serology Mismatched (Donor+/Recipient−) Lung Transplant Recipients. (26th November 2018) - Tomko, Heather; Clancy, Cornelius J; Bryce, Cynthia; Roberts, Mark; Smith, Kenneth; Nguyen, M Hong
Abstract: Background: Cytomegalovirus (CMV) is the most common cause of opportunistic infection (OI) following lung transplant (LTx), with incidence of 30–90%. CMV is associated with direct morbidity and indirect effects (e.g., graft failure, development of OIs and graft rejection (ACR), etc.), all of which lead to poor outcomes. Donor CMV positive, recipient negative (D+/R−) patients have the highest risk of CMV infections, for which they typically receive prolonged durations (≥1 year) of valganciclovir prophylaxis (Px). Px is limited by toxicity and ganciclovir-resistance. We performed a cost effectiveness analysis of differing lengths of Px in CMV D+/R− LTx patients. Methods: We built a Markov state transition model using month-long cycles over a five-year time horizon, a 3% discount rate, and taking a healthcare system perspective. Model health states included episodes of CMV viremia and disease, ACR, and death. Identical hypothetical cohorts of D+/R− patients received 1–2 years of Px. Event probabilities were drawn from national data and local data from patients seen at our center. Cost data (Px and treatment, treatment of side effects, CMV-associated OI, viral load monitoring, etc.) were based on national estimates. Sensitivity analyses were performed on CMV infection incidence while on Px and time on Px. Results: Receiving 1 and 2 years of Px had average total direct medical care costs of 115, 182 and 141, 290, respectively. The average life-years gained for receiving 2 years and 1 year of Px were 3.11 and 2.81, respectively, resulting in an incremental cost-effectiveness ratio (ICER) of 87, 984 per life-year gained. A sensitivity analysis varying CMV infection incidence on Px showed that 1 year dominates 2 years of Px only when this incidence is >50% annually (i.e., 1 year of Px costs less and gains more life years). Real-world experience, however, shows that breakthrough CMV rate while on VGC Px is much <50% due to Px efficacy. If duration of Px is extended to 3 years, the ICER increases to 95, 815/life-year (3.34 life-years gained) when compared with 1 year. Conclusion: A longer duration of Px is predicted to lead to higher overall costs but increased life expectancy for CMV D+/R− mismatch Ltx patients. Px duration > 1 year for these patients may be economically reasonable. Disclosures: C. J. Clancy, Merck: Grant Investigator, Research grant; Astellas: Grant Investigator, Research grant. M. H. Nguyen, Merck: Grant Investigator, Research grant; Astellas: Grant Investigator, Research grant.